تاثير الخرائط الذهنية باستخدام بعض ادوات التعليمية المساعدة في تعلم مهارتي التصويب بداخل و وجه القدم للمبتدئين باعمار ١٢ - ١٤ سنة بكرة القدم - صالح, أ.م.د.زانا محمد محمد (Sulaimani Journal for Humanities, 2023)
• The effect of mental maps using some educational tools to help learn the skills of shooting inside and on the face of the foot for beginners aged 12-14 years in football • Differences between the members of the experimental group that studied according to the strategy of mental maps using some auxiliary educational tools, and the members of the control group that studied according to the method used in learning the skills of shooting inside and on the face of the foot for beginners. The researcher used the experimental method, and the research sample consisted of soccer players aged 12-14 years in Koya Club, who were divided into two groups, an experimental group that used the strategy of mental maps using some auxiliary educational tools, and the control group used the method used, and the research tools included an observation form to evaluate the technical performance in football. Homogeneity and equivalence were carried out in the research variables, and the validity and objectivity of the observation form was confirmed. After completing the application of the experiment and the application of the post-tests, a number of conclusions were reached, the most important of which are: 1- The effectiveness of the strategy of mental maps by using some educational aids and the method used in learning the skills of shooting inside the foot and the face of the foot in soccer. 2- The superiority of the members of the experimental group that studied according to the strategy of mental maps by using some auxiliary educational tools over the members of the control group that studied according to the method used in learning the skills of shooting inside the foot and the face of the foot in football. The researcher recommended the necessity of adopting the strategy of mental maps by using some educational tools to assist in teaching football because of its great impact on learning the skills of shooting inside the foot and the face of the foot in football.